ABOUT THE BOOK OF JESUS CONTRERAS UGARTE: REALITY, POWER, VALUES AND HUMAN RIGHTS: THE DOMINANT POWER IN MAX WEBER - Fernández-Rubalcaba, Eduardo Gago (2019)
The speaker exposes and analyzes the author’s thought of the book Reality, power, values and Human Rights: The dominant power in Max Weber.